FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENOREA PADA SISWI SMAN 1 LOLAK - Strahmawati Hamzah; Hamzah B (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
ABSTRACT Data from the World Health Organization shows that the incidence of dysmenorrhea is quite high throughout the world. The average incidence of dysmenorrhea in young women is between 16,8%-81%. The prevalence of adolescent girls in Indonesia is that the incidence of dysmenorrhea is 64,25%, consisting of 54,89% primary dysmenorrhea and 9,36% secondary dysmenorrhea. The purpose of this study was to analyze the factors associated with the incidence of dysmenorrhea in SMA Negeri 1 Lolak. This study used an analytic observational design with a cross sectional study design with a sample size of 68 respondents. The sampling technique used was total sampling. Data for each variable was collected using a questionnaire through interviews and then the data was then analyzed by univariate and bivariate with chi square test. The results of research conducted at SMAN 1 Lolak showed that there was a relationship between the age of menarche and the incidence of dysmenorrhea in class XI students (p = 0,030 < 0,05), there was a relationship between family history and the incidence of dysmenorrhea in class XI students (p = 0,039 < 0,05), and there is a relationship between exercise habits and the incidence of dysmenorrhea in class XI students (p=0,024